III: LIBERTIES, FRANCHISES, AND RIGHTS. (1st June 2017) - Unknown
Abstract : The people: complaint that, when a free man dies without having produced an heir but has a brother or sister, the king's ministers sell the land or retain it as an escheat, depriving them of their proper inheritance; request for a remedy.